Borderline Pathological Celebrity Worship and Impulsive Buying Intent: Mediating and Moderating Roles of Empathy and Gender - Chen, Outong; Zhao, Xiaojing; Ding, Dongxing; Zhang, Yifan; Zhou, Hongbo; Liu, Ranran (Frontiers in Psychology, 2022)
The present study constructed a moderated mediation model to examine whether borderline pathological celebrity worship may be associated with higher levels of impulsive buying intent. The mediating role of empathy and the moderating role of gender were also examined. 1319 participants recruited from a college through the campus network. The results indicated that (1) borderline pathological celebrity worship could positively predict individuals’ impulsive buying intent; (2) the predictive effect of borderline pathological celebrity worship on impulsive buying intent could be mediated by empathy; and (3) gender moderated the predictive effect of borderline pathological celebrity worship on impulsive buying intent. Specifically, relatively higher levels of borderline pathological celebrity worship were found to be associated with higher impulsive buying intent among men. However, this was relatively less significant among women. Conclusion: The results contribute to previous findings by demonstrating that borderline pathological celebrity worship could affect impulsive buying intent. Moreover, the mediating role of empathy and the moderating role of gender were also revealed.